2020
DOI: 10.1155/2020/5816723
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Stem Cells from the Apical Papilla Promote Dentine-Pulp Complex Regeneration by Inducing Specific Dentinogenesis

Abstract: Regenerative endodontic procedures (REPs) are a new option for the treatment of dental pulp or periapical diseases in permanent teeth with open apices. Histologically, the new tissues formed in the root canal after REPs are mainly cementum- or bone-like mineralised tissues, but not the real dentine-pulp complex. Therefore, how to promote dentine-pulp complex regeneration and improve the clinical effects of REPs has become a prominent research topic. Stem cells from apical papilla (SCAP) are derived from the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 42 publications
(40 reference statements)
1
66
0
Order By: Relevance
“…Zhuang and colleagues showed similar results, with SCAP-derived exosomes increasing the osteogenic potential of BM-MSCs in vitro and in vivo [88]. In Vitro, their results showed that increasing concentrations of exosomes effectively increased mineralization and DSPP expression in BM-MSCs [88].…”
Section: Cell-free Therapy Approaches Using the Dental Stem Cell-derived Secretomementioning
confidence: 84%
See 1 more Smart Citation
“…Zhuang and colleagues showed similar results, with SCAP-derived exosomes increasing the osteogenic potential of BM-MSCs in vitro and in vivo [88]. In Vitro, their results showed that increasing concentrations of exosomes effectively increased mineralization and DSPP expression in BM-MSCs [88].…”
Section: Cell-free Therapy Approaches Using the Dental Stem Cell-derived Secretomementioning
confidence: 84%
“…From 15 publications analyzed, CD105 was described to be expressed on SHED in 14 publications, while CD73 and CD90 were described to be expressed in 9 and 10 publications [58,[66][67][68][69][70][71][72][73][74][75][76][77][78][79]. The analysis of marker expression on SCAP was as follows: 15 publications were analyzed, and the most described markers expressed were CD146 (13), CD73 (8), CD90 (8), and CD105 (8) [27,66,[80][81][82][83][84][85][86][87][88][89][90][91][92]. SCAP is the dental stem cell type where CD146 is described as the most prominent positive marker.…”
Section: Isolation and Characterization Of Stem Cells From Dental Tissuesmentioning
confidence: 99%
“…Functionally, exosomes derived from SCAP were able to promote BMMSC-based dentine-pulp complex regeneration when implanted subcutaneously into immunodeficient mice together with tooth fragments, BMMSCs, and scaffold. Moreover, exosomes derived from SCAP promoted the specific dentinogenesis of BMMSCs [140]. Exosomes also displayed anti-apoptotic activity in odontoblasts.…”
Section: Exosomes Derived From Other Oral Sourcesmentioning
confidence: 92%
“…Moreover, in the same study, it was reported that stem cell proliferation was strongly affected by exosomes. Differentiation towards odontoblasts was also detected in BMMSCs after they were endocytosed (Zhuang et al, 2020).…”
Section: Potential Therapeutic Effects Of Msc-derived Extracellular Vesicles In Regenerative Endodontics and Beyondmentioning
confidence: 95%